Performance of Hereford bulls offered diets based on whole crop silages with or without protein inclusion. (3rd October 2017) - Pesonen, M.; Joki-Tokola, E.; Huuskonen, A.
Abstract : An experiment with 30 Hereford growing bulls was designed to study the effects of (1) forage type and (2) inclusion of rapeseed meal (RSM) in the barley-based concentrate. The three forage types were grass silage (GS), whole crop barley silage harvested at the milk stage (BSM) or at the dough stage (BSD). The concentrate used was rolled barley alone or barley plus RSM. Mean total dry matter (DM) intakes for the GS, BSM and BSD bulls were 9.04, 8.74 and 9.46 kg/day, and carcass gains were 883, 770 and 867 g/day, respectively. Both DM intake and carcass gain were significantly higher in the BSD bulls compared with the BSM bulls. Mean carcass weights of the GS, BSM and BSD bulls were 395, 369 and 392 kg, respectively, and tended to be lower in the BSM bulls. Forage type and RSM had no effects on the carcass conformation or fat score. Rapeseed meal supplementation increased total DM intake (+10%, P <0.01), carcass gain (+14%, P <0.001) and carcass weight (+8%, P <0.01) of the bulls. Overall, GS could be totally replaced by whole crop barley silage in the diet of growing bulls when the concentrate constitutes 0.4 of the diet, but whole crop barley silage should be harvested at the dough stage instead of the milk stage.